A comparison of lansoprazole and omeprazole based triple combinations for the treatment of Helicobacter pylori associated gastritis and peptic ulcer - Yeşim ERALP; Ahmet DOBRUCALI; Nevin BAGATUR; Aykut ÇELİK and Can DAVUTOĞLU and Murat TUNCER and Kadir BAL and Süha GÖKSEL and Hülya UZUNİSMAİL and İbrahim YURDAKUL and; l. (Turkish Journal of Gastroenterology, 2019)
-